Diagnosis of Non-compacted Myocardium of the Left Ventricle in Children - I.B. Yershova; T.F. Osipova; T.V. Nesterova; Ye.V. Chernova; L.I. Gavrysh; B. Kalapala; N.V. Matsyukh; A.S. Karnilovich (Zaslavsky O.Yu., 2014)
The authors presented a review of published literature data on rare congenital abnormalities in children - a non-compacted myocardium of the left ventricle, which refers to unclassified cardiomyopathy. This pathology by the American Heart Association classification relates to genetic cardiomyopathy. Non-compacted myocardium of the left ventricle in children develops due to violation of myocardial induration of the fetus in utero. Diagnosis of the disease is difficult due to the lack of specific clinical signs. The authors also presented a clinical case of non-compacted left ventricular myocardium in 6-year-old girl.